Women and intergenerational masonic networks in Mexico - García Robles, Marco Antonio (2020)
Throughout the 19th century, there were people who held political power in Mexico, whose influence reached regional elites through their positions in the lodges of different rites but also thanks to family networks built around outstanding women in the social sphere. In the present text, a reading of history is explored from the gender perspective. Also, there is an existence of genealogies linked to Freemasonry that is proven.